Pyrrolo[1, 2‐a]quinoxaline‐Based Bipolar Host Materials for Efficient Red Phosphorescent OLEDs. Issue 35 (17th September 2018) - Patil, Bhausaheb N.; Lade, Jatin J.; Vadagaonkar, Kamlesh S.; Chetti, Prabhakar; Chaskar, Atul C.
Abstract: Novel bipolar host materials4CBZ‐PQ, 3CBZ‐PQ andTPA‐PQ based on carbazole, triphenylamine as electron donors and pyrrolo[1,  2‐a]quinoxaline as an electron acceptor unit has been synthesized and characterized. Their photophysical, thermal and electrochemical properties have also been investigated. These structures show suitable frontier molecular orbital (FMO) energy levels and ensure good thermal and morphological stability. Amongst these bipolar host materials, 4CBZ‐PQ showed high Tg (155.7 o C) and Td (160.7 o C) as well as good triplet energy (ET ) of 2.59 eV. Hence, phosphorescent organic light‐emitting diodes (PhOLEDs) were fabricated containing4CBZ‐PQ, 3CBZ‐PQ andTPA‐PQ as host materials.4CBZ‐PQ showed best EL performance with a turn‐on voltage of 2.6 V, a maximum brightness of 100388 cd/m 2, a maximum current efficiency of 18.1 cd/A 1, a maximum power efficiency of 12.9 lm/W and an external quantum efficiency of 15.1%. The RBY (red, brown and yellow) three‐color PhOLED with4CBZ‐PQ as the host material showed maximum external quantum efficiency of 15.1% for the red device, indicating its potential utility as a host material for highly efficient PhOLEDs. Abstract : The synthesis of novel bipolar host materials involving triphenylamine, carbazole as electron donors and pyrrolo [1,  2‐a]quinoxaline as an electron acceptor is carried out. The molecules showed good thermal and morphological stabilities, triplet energy (2.59‐2.77 eV), as well as external quantum efficiencies (0.089‐15.1%) for red PhOLEDs with low efficiency roll‐off.